PEMBANGUNAN INTEGRITAS APARATUR DESA DI KANTOR DESA CIBADUNG KECAMATAN GUNUNG SINDUR, KABUPATEN BOGOR - Waluyo Waluyo; Harjoyo Harjoyo; Sugiyarto Sugiyarto (Universiitas Pamulang, 2023)
ABSTRACT Partners in this community service activity are staff/apparatus of Cibadung village, Gunung Sindur District, Bogor Regency such as village heads, section heads (Kasie), heads of affairs (Kaur), hamlet heads (Kadus). The location of the partners is at Jalan Pendidikan RT 003/03 Gunung Sindur, Bogor 16340. The main problems faced by partners are low work discipline, selective work, uneven skills, not optimal attendance levels, and weak supervision from leaders. Method of implementation PKM activities use the Participatory Learning and Action (PLA) method or a participatory learning and practice process in the form of counseling, role playing training and simulations on building the integrity of village officials in carrying out their responsibilities as village community servants. The result of this activity is that village staff/apparatus have motivation, integrity and responsibility, apply the principle of